An opportunistic routing solution to monitor isolated elderly people in rural areas - Jesús-Azabal, Manuel (2020)
Countries are experiencing a global population ageing. It is estimated that the percentage of third age people will notably increase in next decades, implying a difficult challenge to society. Rural areas are the most affected locations by these conditions. Currently, small vil- lages are facing an increasing ageing of population where almost 40% of inhabitants are over 65. Medical needs are one of the most relevant aspects in this context. This factor, in conjunction with other reasons such as loneliness, motivates technological solutions. Despite this, Inter- net is not accessible from rural and low income areas, due to the lack of interest from the operator side to invest in these locations. In this paper, an opportunistic routing solution based on BLE is proposed, with the aim of monitoring loneliness population in order to detect potential emergencies.